The Problem of Food Waste in Different Types of Households on the Example of the Residents of Poland and Polish People Residing in the United Kingdom – Pilot Study - Magdalena Skotnicka; Kaja Karwowska; Maria Śmiechowska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The objective of this study was comparing the scale of food waste depending on different types of households among Poles living in Poland and in the UK. The research was conducted in the group of 622 persons, whereas 345 persons lived in Poland and 277 were residing in the UK for minimum 2 years, however not longer than 10 years. The respondents were differentiated depending on the type of the household in which they lived: 1-person, 2-person, 3-person, 4-person and more. More than the half of the respondents declared that they had happened to throw away food, whereas these are the “British” Poles who waste food most and who are comprised in 1- and 2-person households. A significant dependence was observed in both studied groups, the more numerous the household was the lesser amount of food was wasted. The mostly wasted food included bread, yoghurts, sausage, fruit and vegetables, regardless of the number of persons in the given household or of the place of residence. Due to the fact that the rate of food waste is so high, it is necessary to find a way to implement new ideas and interventions which would limit the food waste in the households.